Feederism Eating, Weight Gain, and Sexual Pleasure - Charles, Kathy; Palkowski, Michael; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2015)
This book explores the controversial and misunderstood world of sexualised weight gain known as feederism. Conversations with over 20 feeders and feedees are analysed through a psychological and sociological lens. The implications for health professionals working in bariatrics are discussed along with directions for future research.
Keywords: Sexual behavior; Sexual psychology; Sociology; Psychology, Pathological; Social structure; Social inequality; Cultural studies; Social groups; Family; Sexual Behavior; Gender Studies; Psychopathology; Social Structure, Social Inequality; Cultural Studies; Sociology of Family, Youth and Aging